Pemanfaatan Web Application Dalam Peningkatan Efisiensi dan Efektifitas Kerja Administrasi (Studi Kasus: Pemesanan dan Pembuatan Surat Keterangan) - Reina, Reina (Bina Nusantara University, 2010)
The purpose of this study was to determine the extent to which the use of a web application to improve efficiency and effectiveness of administrative work. The research method used consisted of the analysis phase, study libraries to support application design and data collection based on observations. Results of evaluation and observation data before and after implementation of the system showed that the use of a web application to improve efficiency and effectiveness of administrative work, e.g. by decreasing the length of time the making of letter, an increase in the percentage of the making of timeliness, accuracy of data validation and provide facilities for students in order letter as well as convenience for staff in the making of letter. Another thing is the ease in monitoring the accuracy of the making of letter.